Needs and Preferences in Learning English: Case Study of Informatics Students - Sri Rejeki; Dwi Iswahyuni (ITScience (Information Technology and Science), 2024)
Learning English has become increasingly vital for informatics and information systems students, particularly as it impacts their academic and professional prospects. This study aims to explore the needs and preferences of students in these fields regarding English language instruction, highlighting the importance of tailored educational approaches. The research involves a mixed-methods approach, combining quantitative questionnaires and qualitative interviews with 56 students from Universitas Muhammadiyah Surakarta and Universitas Bina Sarana Informatika. The findings reveal that while students generally feel